SCIENTIFIC ANALYSIS OF THE PROCEDURE FOR PREPARING THREADS FOR THE WEAVING PROCESS - Toshtemirov Qosimjon Abdullaxayevich (European Science Publishing, 2023)
In the article, the method of preparation of yarns for the weaving process, and the physical and mechanical properties of the yarns are analysed by comparing them with the properties of ordinary weaving yarns of the enterprise. According to the results of the research, the yarns in the weaving of gauze knitwear and textile products are formed by the interweaving of individual threads in a certain composition. One of the threads passes over or under the other, at a right angle It was found out in the results of the research that it is of high quality and strong when it is woven in a straight line.
Keywords: textile yarn, grain, hairiness, cookedness, roughness, breaking strength, product, quality, carding, re-carding, carding.